A Review: Accelerated Stability Testing and Shelf-Life Prediction of Pharmaceutical Products Using The Arrhenius Equation - Bhima Sakti; Ahmad Hisyam Ammar; Maya Salsabila; Ferdinan Pradana Putra; Bikhnadza Syabina Ragil; Malehkasari Mulyaningsih; Anindya Raina Paramesti (Devotion : Journal of Research and Community Service, 2026)
Drug stability is an important parameter in ensuring the quality, safety, and effectiveness of pharmaceutical preparations during storage. Conventional stability testing requires a long period of time; therefore, accelerated stability testing methods based on the Arrhenius equation have been developed to accelerate the prediction of drug shelf life. This review article aims to examine the application of Accelerated Stability Testing (AST), Accelerated Shelf Life Testing (ASLT), Accelerated Predictive Stability (APS), and the Accelerated Stability Assessment Program (ASAP) in predicting the stability of various pharmaceutical dosage forms. The research method used was a narrative literature review, analyzing 10 national and international original research articles published between 2016 and 2026, obtained from Google Scholar, ScienceDirect, PubMed, and MDPI databases. The results of the review showed that the Arrhenius approach was able to provide accurate shelf-life predictions for liquid, semisolid, solid, biological, and herbal dosage forms. Temperature, humidity, oxygen exposure, and packaging type were identified as factors affecting the degradation rate of pharmaceutical products during storage. In addition, Arrhenius-based predictive stability models were considered effective in accelerating product development and supporting pharmaceutical registration processes. In conclusion, the Arrhenius kinetic approach is an efficient and valid method for stability evaluation and shelf-life prediction of modern pharmaceutical products.